Parents' knowledge and practices of child eye health care: A scoping review. - Nor Diyana Hani Ghani; Norliza Mohamad Fadzil; Zainora Mohammed; Mohd Harimi Abd Rahman; Normah Che Din (PLoS ONE)
Background Treating children's eyes is not just a privilege for a child, it is an essential requirement for their visual health. Parents, as caregivers, have a paramount responsibility to make decisions regarding their children's eye health. Thus, this review aims to identify and summarise published information about parents' knowledge and practices on children's eye health care. Methods Relevant articles searches were performed through a systematic search of databases (EBSCOhost, PubMed, and Scopus) using the keywords 'knowledge', 'practice', 'parent', 'eye', 'problem', and 'children'. This review was conducted and reported in line with the PRISMA-ScR. The methodological quality of the listed studies was assessed using A Modified McMaster Critical Review form based on the total score. Result From a total of 235 studies retrieved through literature review and pearling, 219 remained after removing duplicates. After screening titles and abstracts, 204 irrelevant studies were excluded, leaving 15. After a detailed full-text review, four studies were excluded due to not meeting inclusion criteria. Thus, this review includes the remaining 11 studies. All eleven studies (n = 11) show that parents's knowledge and practices vary. Some parents display good knowledge regarding children's eye health care, for example, understanding the importance of wearing spectacles, the significance of children having normal vision, and where to seek eye examinations. Five studies (n = 5) showed that parents have good practices such as consulting doctors and seeking eye examinations and treatment at the hospital. Six studies (n = 6) showed that parents have misconceptions regarding knowledge, practices, and treatment of children's eye health. Conclusion This scoping review found that parents' knowledge and practices regarding children's eye health are poor. Parents' perceptions and practices about the cause and treatment of eye problems were tainted with misconceptions. Therefore, implementing structured programs to enhance awareness and promote the adoption of healthy practices for children's eye health is required.